A Rare Tumor Case in an Adult Patient with Neurofibromatosis: Lumbar Ependymoma - Yakar, H.; Ertugrul, B.; Kaplan, M. (Wolters Kluwer Medknow Publications, 2022)
In patients with type 1 neurofibromatosis (NF1), there is an increased susceptibility to tumor development in the central nervous system due to the loss of neurofibromin, an inactivator of the protooncogene Ras. NF1 has a broad clinical spectrum,which includes spinal tumors. Although the most common intramedullary tumor of the spinal cord in adults is ependymoma, few patients with NF1 accompanied by spinal ependymoma have been reported to date, and the localization of the tumors is cervical and thoracic in these cases. In this study, we report the case of a patient with NF1 presenting to our clinic with low back pain and gait disturbance. The patient had an intradural extramedullary ependymoma at the L2-3 vertebra level. This report is the first case of NF1 with spinal ependymoma localized in the lumbar region.
Keywords: Ependymoma; neurofibromatosis; spine